<span>The object's speed is 8/5 miles per hour or 1.6 mph.</span>
Answer:
![f''(x)=f''(-x)](https://tex.z-dn.net/?f=f%27%27%28x%29%3Df%27%27%28-x%29)
Step-by-step explanation:
A function satisfying the equation
is said to be an even function. This denomination comes from the fact that the same relation is satisfied for functions of the form
with
even. Observe that if
is twice differentiable we can derivate using the chaing rule as follows:
implies ![f'(x)=f'(-x)\cdot (-1)=-f'(-x)](https://tex.z-dn.net/?f=f%27%28x%29%3Df%27%28-x%29%5Ccdot%20%28-1%29%3D-f%27%28-x%29)
Applying the chain rule again we have:
implies ![f''(x)=-f''(-x)\cdot (-1)=f''(-x)](https://tex.z-dn.net/?f=f%27%27%28x%29%3D-f%27%27%28-x%29%5Ccdot%20%28-1%29%3Df%27%27%28-x%29)
So we have that function
is also an even function.
Answer is to the question is 20
Answer:
Its a right triangle
Step-by-step explanation: